Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2016)
This Work Program (WP) translates the policy priorities and strategic directions laid out in the Fall 2016 Global Policy Agenda (GPA) and the International Monetary and Financial Committee (IMFC) Communique into an Executive Board agenda for the next six-twelve months. The Managing Director's GPA called on members to use a balanced mix of all policy tools to revive demand and raise productivity, and ensure that gains from technology and globalization are shared more broadly. The GPA also warned against retreating from multilateralism at a time when cooperation and coordination are critical. It outlined how the Fund would support the membership by helping policymakers identify policy space and enhance resilience; assisting in understanding and tackling the underlying causes of low productivity growth; supporting members to expand economic opportunities-including by ensuring adequate and effective safety nets; and advocating for multilateralism that works for all. Where the work extends beyond traditional areas, the WP will focus on issues with a macro-economic impact that are systemically important or relevant for many and amenable to change through economic policies.